2020
DOI: 10.1126/science.aaz7548
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme A from cytotoxic lymphocytes cleaves GSDMB to trigger pyroptosis in target cells

Abstract: Cytotoxic lymphocyte–mediated immunity relies on granzymes. Granzymes are thought to kill target cells by inducing apoptosis, although the underlying mechanisms are not fully understood. Here, we report that natural killer cells and cytotoxic T lymphocytes kill gasdermin B (GSDMB)–positive cells through pyroptosis, a form of proinflammatory cell death executed by the gasdermin family of pore-forming proteins. Killing results from the cleavage of GSDMB by lymphocyte-derived granzyme A (GZMA), which unleashes it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
822
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 914 publications
(930 citation statements)
references
References 59 publications
15
822
1
Order By: Relevance
“…This indicated that we could not exclude the pyroptotic role of other members of the gasdermin family, like GSDMA, GSDMB, and GSDME, which also display pore-forming and pyroptotic activity. [40][41][42] Further analysis revealed that PPE13 was localized to the surface of cells, which is consistent with results of a previous study. 20 The presence of PE/PPE proteins on the cell surface might enable them to directly interfere with host innate immune pathways.…”
Section: F I G U R E 4 Ppe13supporting
confidence: 91%
“…This indicated that we could not exclude the pyroptotic role of other members of the gasdermin family, like GSDMA, GSDMB, and GSDME, which also display pore-forming and pyroptotic activity. [40][41][42] Further analysis revealed that PPE13 was localized to the surface of cells, which is consistent with results of a previous study. 20 The presence of PE/PPE proteins on the cell surface might enable them to directly interfere with host innate immune pathways.…”
Section: F I G U R E 4 Ppe13supporting
confidence: 91%
“…This study centers on the experimental broad-spectrum DPP inhibitor BXCL701 (also named VbP, PT-100, or Talabostat) that was recently assigned orphan drug designation for the treatment of AML by the FDA, and is based on recent findings showing that VbP/BXCL701 and more selective DPP8/DPP9 inhibitors are potent inducers of pyroptosis in AML cell lines and in primary AML samples from patients. 164 Several recent studies showed that enforced activation of Gasdermin family members in cancer cells enhanced immune cell-mediated tumor clearance in mouse models, [165][166][167] adding credence to the notion that pyroptosis induction may enhance cancer immunotherapies to the benefit of patients.…”
Section: G S Dmd -The Ne W K Id On the B Lo Ckmentioning
confidence: 98%
“…In addition, our results employing an inhibitor of extracellular GzmA, Serpinb6b, in vitro and in vivo, strongly suggest that GzmA enhances the inflammatory pathological response in sepsis in the extracellular space. Thus, since Serpinb6b should not affect intracellularly perforindelivered GzmA, we suggest that GzmA does not contribute to sepsis by promoting pyroptosis (Zhou et al, 2020) or other types of cell death (Susanto et al, 2013). This suggestion is further supported by our results showing increased levels of extracellular GzmA in serum from patients with abdominal sepsis.…”
Section: Discussionmentioning
confidence: 83%